PENGARUH PEMBERIAN LEAFLET DAN PENJELASAN TERHADAP PENGETAHUAN IBU MENGENAI HIPERBILIRUBINEMIA NEONATORUM - Belia Dwi Hapsari Nugraheni; Adhie Nur Radityo Suswihardhyono (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2016)
Background : Hyperbilirubinemia is one of the most common clinical phenomenon found in neonates marked yellow coloration of the skin, mucosa, sclera result of the accumulation of direct and indirect bilirubin in serum or blood, if levels reach 5-7mg / dL and could have an impact on infant mortality if handling less. However, mothers' knowledge of hyperbilirubinemia is still low. So it takes a method of counseling to increase knowledge of mothers about hyperbilirubinemia.Aim : Analyzing the effect of leaflets and an explanation of the mothers knowledge regarding neonatal hyperbilirubinemia.Method : This study used a quasi-experimental with pretest posttest group. Samples taken counsecutive sampling. There are 35 subjects of mothers who gave birth at the Hospital dr. Kariadi, Semarang from May to June 2015. The researchers gave questionnaires that have been tested for validity as a pretest and then the subject was given a leaflet and explanations after pretest done. Posttest conducted one day after the subjects were counseled on neonatal hyperbilirubinemia. All result were analyzed using the Wilcoxon test..Result : This study, the mean maternal age 29.97 ± 7.09 years and the majority of respondents are housewives amounted to 48.60%. Knowledge mean of 5.82 ± 4.68 before being given a leaflet and explanations, can be increased significantly to 14 ± 2.99 at posttest, after being given leaflets and explanations with a value of p <0.05.Conclusion : Methods of individual counseling with the help of leaflets can increase knowledge about the mother neonatal hyperbilirubinemia.